Protocollo operativo per la validazione geometrica di immagini satellitari ad alta risoluzione - Crespi, Mattia; De Paulis, Riccardo; Gini, Rossana (GEOmedia, 2016)
In recent years, the increasing availability of scenes captured by high-spatial resolution satellites (such as GeoEye-1, WorldView-1 and Pleiades-2 or 1A and 1B) has opened new application scenarios realizable to a littlemid scale, bringing the Remote Sensing more near to Photogrammetry. Starting from satellite images, it is now possible to generate map products (ortho) of the earth's surface, manageable within GIS software and suitable to constitute base maps of geographic information systems.